Inovasi Permen Jeli Jamu: Mendorong Semangat Kewirausahaan Siswa Sekolah Dasar - Nugraheni, Krisnawati Setyaningrum; Palupiningtyas, Dyah; Wijoyo, Tuwuh Adhistyo; Intiar, Septa; Cahyaningtyas, Frisca Dwi; Yosiano, Theofilus Christo (Jurnal Abdimas Multidisiplin, 2024)
Purpose: This community engagement program aims to cultivate entrepreneurship spirit among elementary school students through two primary approaches: Introduction to Family Medicinal Plants (Tanaman Obat Keluarga or TOGA) and training in making herbal jelly candy from raw materials such as ginger, turmeric, and tamarind, as well as Entrepreneurship Capacity Building Training and practical market day exercises. Methodology: The methods employed include the Introduction to Family Medicinal Plants (Tanaman Obat Keluarga or TOGA) and training in making herbal jelly candy from raw materials such as ginger, turmeric, and tamarind, as well as Entrepreneurship Capacity Building Training and practical market day exercises, where the delivery of the material is conducted through lectures and practical exercises. Results: An impressive 95% of these students gained an understanding of various Family Medicinal Plants (TOGA) and their benefits, mastering the art of crafting and creatively packaging herbal jelly candy. Moreover, 85% of the students showed keen enthusiasm by practicing the production of healthy herbal jelly candy at home. Additionally, the program ensured the full participation of all students in Entrepreneurship Capacity Building training, where both students and teachers comprehensively embraced market day practices. Limitations: In a span of 1-2 weeks, this program successfully engaged 60 fourth-grade students from SD Labschool Unnes, achieving remarkable outcomes Contribution: This program offers students a chance to learn essential business skills like production planning, inventory management, and marketing strategies, thus promoting entrepreneurship among young learners while emphasizing the importance of healthy eating.